VARIABILITAS KEKUATAN KAYU PADA POHON MAHONI - Suparman Karnasudirdja (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
A study on a variation of bending and compression parallel to the grain strength in Mahogany (Swietenia mahogany) tree has been under taken. The material consisted of 5 trees, each of which was represented by 4 bolt taken respectively from near tree base, at middle half and upper end of the merchantable bole. The test pieces were then drawn from each bolt following the cruciform pattern of the ASTM D14362 procedure. Using this pattern, 221 and 197 test specimens were respectively obtained for the bending and compression test. The result shows that the tree averages of the bending strength ranges from 90 - 110% of the species maan value, the cardinal point averages from 100 -101% and the position within tree (bolt) averages from 97 - 102%, As has been anticipated the tree averages are significantly different in both the bending and compression strengths. Computation of the precision of estimates of the species mean in term of the probable limit of error (PLE) as percentage of the species mean within 95% confidence band as suggested by Pearson (1952) indicates an error of 9,51% and 12,44% for respectively the bending and compression strength. Values of the probable limit of error PLE were then calculated using various combination of number of test pieces per tree and number of trees, and the result compared with those obtained from previous test using Agathis lorantifolia and Schima wallichii tree species. It shows that for structural and non-structural purposes at leat 10 trees per species, and 5-10 specimens per tree should be employed in future strength test in order to obtain an error of between 5 -10%. This is definitely an advantage compared with the current procedure.